2015
DOI: 10.1002/2014jb011668
|View full text |Cite
|
Sign up to set email alerts
|

U‐Pb dating of interspersed gabbroic magmatism and hydrothermal metamorphism during lower crustal accretion, Vema lithospheric section, Mid‐Atlantic Ridge

Abstract: New U/Pb analyses of zircon and xenotime constrain the timing of magmatism, magmatic assimilation, and hydrothermal metamorphism during formation of the lower crust at the Mid-Atlantic Ridge. The studied sample is an altered gabbro from the Vema lithospheric section (11°N). Primary gabbroic minerals have been almost completely replaced by multiple hydrothermal overprints: cummingtonitic amphibole and albite formed during high-temperature hydration reactions and are overgrown first by kerolite and then prehnite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 150 publications
4
6
0
Order By: Relevance
“…The presence of inherited zircons is consistent with previous evidence for anomalously old gabbro and inherited zircons at Atlantis Bank (Schwartz et al, 2005) and on other ridges (Lissenberg et al, 2009;Rioux et al, 2012Rioux et al, , 2015b. Schwartz et al (2005) found that zircon 206 Pb/ 238 U dates from four surface gabbros were older than both the 206 Pb/ 238 U dates of nearby samples and the predicted magnetic age.…”
Section: Origin Of the Xenocrystic Zirconssupporting
confidence: 88%
“…The presence of inherited zircons is consistent with previous evidence for anomalously old gabbro and inherited zircons at Atlantis Bank (Schwartz et al, 2005) and on other ridges (Lissenberg et al, 2009;Rioux et al, 2012Rioux et al, , 2015b. Schwartz et al (2005) found that zircon 206 Pb/ 238 U dates from four surface gabbros were older than both the 206 Pb/ 238 U dates of nearby samples and the predicted magnetic age.…”
Section: Origin Of the Xenocrystic Zirconssupporting
confidence: 88%
“…The high-temperature NMB crystals appear to correlate with lower δ 18 O values (Supplementary data). The low temperatures for most of the CAMP samples are consistent with those found in zircon from mid-ocean ridge gabbros (Rioux et al 2015b) and gabbro intrusions (Fu et al 2008). They are also consistent but slightly higher than the Ti temperatures from quartz crystals (calculated assuming the same Ti activity of 0.6) found in the same evolved granophyric pockets as the zircon crystals (Fig.…”
Section: Trace Elements In Zircon and Ti In Quartzsupporting
confidence: 80%
“…Considering the progressive mylonitization and recrystallization of the protoliths with release of U, Th and REE from decomposing igneous minerals on the one hand, and the rise in the U-Th-Pb and REE concentrations between the metamorphic populations as well as the fluid-assisted dissolution-reprecipitation process that created the predominant population of metamorphic zircon on the other hand, we interpret the metamorphic zircon populations as products of near-peak and retrograde metamorphism. The elevated Th/U ratio and the less negative Eu anomaly in the retrograde metamorphic zircon population imply higher redox conditions with increasing oxidation of U 4+ to less zircon-compatible U 6+ (see Rioux et al, 2015), and of Eu 2+ to Eu 3+ that partitions preferentially into zircon. An unzoned zircon core with a U-Pb age of 380 ± 9 Ma represents the near-peak metamorphic population but has U, Th and REE concentrations rather similar to those of the protolith zircon (Table 1, Appendix S9) from which the trace element composition seems to be inherited (see Goodge, Fanning, & Bennett, 2001;Kryza & Fanning, 2007).…”
Section: Metamorphic Evolutionmentioning
confidence: 99%